Wybory czerwcowe 1989 roku we współczesnych podręcznikach do nauczania historii w szkole podstawowej - Białokur , Marek; Biedka , Karolina; Gołębiowski , Dariusz (Studia Edukacyjne, 2024)
The aim of the article is to analyses how the first partially free parliamentary elections held in the People’s Republic of Poland on 4 June 1989 are presented in primary school history textbooks today. The June elections were the first ones in Central and Eastern Europe won by the anti-communist opposition. This took place before the fall of the Berlin Wall. Influenced by the ongoing discussions about whether 4 June should be recognized as a national holiday, we decided to investigate how young people learn about these events. Textbooks are a major research material because they are still the most widely used medium in the educational process and often the only source of students’ knowledge of history. We analyzed all textbooks currently approved by the Ministry of National Education for use in schools for grade 8 of primary school.